Personal Hygiene Education Sebagai Persiapan Menghadapi Menstruasi Di Wilayah Punggur Kecil Kecamatan Sungai Kakap Kabupaten Kubu Raya - Surtikanti; Ariyanti, Sri; Kardiatun, Tutur; Wahyuni, Tri; Makmuriana, Lestari; Kuswida Bhakti, Wida (Indra Institute Research & Publication, 2023)
Menstrual Hygiene Management (MHM) is an important issue related to the education, health, and dignity of young women and adult women in Indonesia (Unicef, 2017). UNICEF research in Indonesia (2015) found that 1 in 6 girls experience problems during menstruation, one of which is the absence of proper latrines in schools, the unavailability of water for self-cleaning and blood-stained skirts, the unavailability of spare pads when needed, and unavailability of trash cans and wrappers to dispose of used sanitary napkins. Data shows that 1 in 4 girls never discuss with friends or parents about menstruation before getting their first menstruation, Taboos and stigma also make limited the activities of female students during menstruation (Women and Child Protection, 2021). The purpose of this community service program is to provide counseling to school-age children about reproductive organ hygiene, provide education on how to clean the reproductive organs during menstruation and change adolescent behavior towards clean and healthy living behaviors. The method of implementing this Community service program is by providing education to adolescents. This activity was carried out from January to March 2022 in Punggur Kecil Village, Sungai Kakap District, Kubu Raya Regency.